2006
DOI: 10.1159/000094218
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cytogenetic studies towards the full karyotype analysis of human blastocysts and cytotrophoblasts

Abstract: Numerical chromosome aberrations in gametes typically lead to failed fertilization, spontaneous abortion or a chromosomally abnormal fetus. By means of preimplantation genetic diagnosis (PGD), we now can screen human embryos in vitro for aneuploidy before transferring the embryos to the uterus. PGD allows us to select unaffected embryos for transfer and increases the implantation rate in in vitro fertilization programs. Molecular cytogenetic analyses using multi-color fluorescence in situ hybridization (FISH) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 89 publications
(38 reference statements)
0
15
0
2
Order By: Relevance
“…For example, segmental aneuploidy is frequent in yeast deletion mutants [39] and can confer a growth advantage to the aneuploid cells compared to the euploid ones [39]. In humans, aneuploid cells have recently been found to be an integral part of the functional pool of neurons and in placental trophoblasts, consistent with a functional role for aneuploidy in these contexts [12][13][14][15]. In plants, it is believed that aneuploidy can play a role in speciation and phenotype evolution [40].…”
Section: What Are the Evolutionary Consequences Of Surviving Dosage Imentioning
confidence: 97%
See 1 more Smart Citation
“…For example, segmental aneuploidy is frequent in yeast deletion mutants [39] and can confer a growth advantage to the aneuploid cells compared to the euploid ones [39]. In humans, aneuploid cells have recently been found to be an integral part of the functional pool of neurons and in placental trophoblasts, consistent with a functional role for aneuploidy in these contexts [12][13][14][15]. In plants, it is believed that aneuploidy can play a role in speciation and phenotype evolution [40].…”
Section: What Are the Evolutionary Consequences Of Surviving Dosage Imentioning
confidence: 97%
“…For example, aneuploid cells are normally found in certain tissues such as the brain and the placenta, where they appear to play a functional role [12][13][14][15]. Aneuploidy has been associated with invasive cancer [16,17] and controversially proposed to play a causal role in malignancy [18].…”
Section: Introductionmentioning
confidence: 99%
“…До 50-70% эмбрионов явля-ются анеуплоидными, представляя, таким образом, случаи нестабильного генома в результате мейотиче-ского нерасхождения [4,10,[32][33][34][35]. Однако подавля-ющее большинство анеуплоидных эмбрионов, веро-ятно, спонтанно абортируются на последующих стадиях развития [9,23,35].…”
Section: нестабильность соматического генома во время пренатального рunclassified
“…До 50-70% эмбрионов явля-ются анеуплоидными, представляя, таким образом, случаи нестабильного генома в результате мейотиче-ского нерасхождения [4,10,[32][33][34][35]. Однако подавля-ющее большинство анеуплоидных эмбрионов, веро-ятно, спонтанно абортируются на последующих стадиях развития [9,23,35]. Тем не менее, исследование преим-плантационных эмбрионов, которые демонстрируют геномную нестабильность на следующих онтогенетиче-ских стадиях, выявляет почти во всех образцах возникно-вение анеуплоидии или хромосомных аберраций, затра-гивающих не менее 20-50% клеток [8,32,36].…”
Section: нестабильность соматического генома во время пренатального рunclassified
“…In our studies of uncomplicated pregnancies, we did find that a majority of iCTBs identified as human leukocyte antigen -G (HLA-G) positive cells [21] were chromosomally abnormal [38][39][40]. Please note that this population is rarely studied by any means, because of the difficulty of obtaining these samples.…”
Section: Pregnancymentioning
confidence: 99%